Evaluation of alternative treatments for Acanthoscelides obtectus (Say) (Coleoptera: Bruchidae) control - Bavaresco, Alvimar (Revista de Ciências Agroveterinárias, 2007)
The bean weevil Acanthoscelides obtectus (Say) (Coleoptera: Bruchidae) can cause severe damages in bean grains, compromising the nourishing quality and its use as seed. The pest damages can reach 100% in stored product. The objective of this research was to evaluate the efficiency of alternative treatments: diatomaceous earth (Insecto® and Bugram Protect® –1 g/Kg), hydrated lime (6 g/Kg), dolomitic lime (200 g/Kg), wood ash (200 g/Kg), sand (200 g/Kg), bean residue (200 g/Kg), neem oil 1% (5 mL/Kg) and soybean oil (2.5 mL/Kg) on the control of A. obtectus in stored bean seeds. Diatomaceous earth (Insecto® and Bugram Protect®), wood ash, hydrated lime and dolomitic lime promoted high mortality of A. obtectus adults after 96 hours of the application, showing 93.8% to 100.0% control efficacy. These products also protected efficiently bean seeds from the bean weevil damages for a 240 days storage period. On the other hand, bean residue and soybean oil were not efficient against the bean weevil, while neem oil and sand showed intermediate control, reducing the population increase and the insect damage in relation to the control.